Space odyssey. - Malin, David; Osaka, Eriko (Mito : Art Tower Mito - Contemporary Art Gallery, 2001)
McCracken, John ; Subaru Telescope ; Ruff, Thomas ; Wenyon & Gamble ; Light, Michael ; Malin, David ; Moriwaki, Hiroyuki ; Shannon, Thomas ; Kanayama, Akira ; Hubble Space Telescope ; Hirano, Jiro ; Eames, Charles & Ray ; Reference Materials
Engels & Japans
Space Odyssey, Contemporary Art Center Art Tower Mito, Mito, February 10 - May 6, 2001
boek